Synthesis And Electrochemical Properties Of Licoo2 Cathode With Graphite Or Graphene Anode For Aqueous Rechargeable Lithium Batteries - Aziz, Nur Azilina Abdul (2018)
Aqueous rechargeable lithium battery is currently receiving attention due to its lower manufacturing cost and improved safety of energy storage. The cathode material with the selection of the appropriate synthesis parameters is one of the factors that will produce good material properties and simultaneously achieve a good electrochemical performance. In this study, effects of stirring times and sonication times were employed on LiCoO2 synthesized via sol-gel method. The results of material characterization between optimum stirring time (30 hours) and optimum of sonication time (120 minutes) showed the sample synthesized via sonication process better than stirring process with good crystallinity and smallest particle size. Morphological analysis showed the particle size distribution located in the range of 0.29-0.43 μm. The cycle behaviour of optimum LiCoO2 synthesized via sonication with graphene as anode exhibited better cycling stability, well-defined redox peaks and a smaller potential difference (0.13 V). The performance of the LiCoO2 batteries showed an outstanding enhancement of specific discharge capacity (122.43 mA h g-1 at 0.5 C) and reversibility in an aqueous electrolyte. The improvement in the electrochemical performance was supported by the impedance analysis. A small difference (0.7 ) in the charge transfer resistance before and after a charge-discharge analysis indicated that the Li+ ions had been well-diffused during the intercalation/de-intercalation process.